2004
DOI: 10.1097/01.sla.0000128687.59439.d6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Micrometastatic Breast Cancer in Histopathology-Negative Axillary Lymph Nodes Correlates With Traditional Predictors of Prognosis

Abstract: This is the first report to show that overexpression of breast cancer-associated genes in breast cancer subjects with pathology-negative ALN correlates with traditional indicators of disease prognosis. These interim results provide strong evidence that molecular markers could serve as valid surrogates for the detection of occult micrometastases in ALN. Correlation of real-time RT-PCR analyses with disease-free survival in this patient cohort will help to define the clinical relevance of micrometastatic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 32 publications
7
94
1
Order By: Relevance
“…The real malignant potential of these cells is not yet known. Nevertheless, as some limitations were observed in our study, more investigations are required to confirm our results by including more patients, especially with advanced-stage breast cancer, and by increasing the sensitivity and specificity of screening methods using a multimarker PCR approach [20] associated with xenografting experiments. Only then can ovarian tissue transplantation be contemplated in patients with advancedstage disease.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The real malignant potential of these cells is not yet known. Nevertheless, as some limitations were observed in our study, more investigations are required to confirm our results by including more patients, especially with advanced-stage breast cancer, and by increasing the sensitivity and specificity of screening methods using a multimarker PCR approach [20] associated with xenografting experiments. Only then can ovarian tissue transplantation be contemplated in patients with advancedstage disease.…”
Section: Resultsmentioning
confidence: 76%
“…In the existing literature on axillary sentinel lymph nodes in breast cancer patients [20,34,46], the discrepancy between histological and immunohistochemical analyses and PCR approaches has already been described. It is most likely explained by the sampling procedure, because the parts of the lymph node analyzed using molecular techniques are different from those examined by histopathology and immunohistochemistry.…”
Section: Quantitative Pcr Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammaglobin-1 and -2 were amplified in additional 30.1 and 17.8% of the H&E-negative nodes. In an interim analysis of a multi-institutional study of multimarker RT -PCR of H&E-negative lymph nodes (Gillanders et al, 2004), a correlation between PCR positivity and other well-established prognostic markers including histological grade and St Gallen risk category was reported. This study also showed mammaglobin to be the most informative marker in their multimarker panel.…”
Section: Discussionmentioning
confidence: 99%